Developing E-book Batang Heaven of Asia as Descriptive Text Teaching Material - Sri Rizkiyah; Inayatul Ulya; Rizka Hayati (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
Technology in this era as a friend for human. It can be good or bad depending on the user. Now almost of all generation prefer the practical thing to use in their life, included in learning process. Both of teachers and students prefer to have an effective and efficient learning process. The researcher use the situation to conduct research and development. The research “Developing Ebook “Batang Heaven of Asia” as Descriptive Text Teaching Materials” was the utilization of technology in learning process. The e-book can help the teachers and the students as learning source. The research answered two questions (1) How is the need of developing e-book “Heaven of Asia” as descriptive text teaching materials? (2) How is developing e-book “Batang Heaven of Asia” as descriptive text teaching materials? The development procedures that used in this research was PPE from Richey and Klein 2005 . Those procedures were planning, production, and evaluation. In planning, the researcher distributed the questionnaire to get teachers’ and students’ needs. From the data result, the researcher analyzed the data and designed the product based on teachers’ and students’ needs. The process of producing this e-book, the researcher observed the tourism destination before writing the text. The title of e-book was Let’s Explore Batang. It contained the basic standard and learning goals, the materials, the texts, worksheet and glossary. This RND arrange e-book as descriptive text teaching material based on description of tourism destination in Batang Regency. This e-book was not only the texts but there were some pictures of the destination described. The e-book validated by some experts, they were English lecturers and English teacher. Keywords: e-book, RND, needs analysis, materials